Narasi Adaptasi Budaya Xaviera di Korea Selatan: Analisis Paradigma Naratif pada Podcast - Sherina, Putri; Hanafi, Des (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2024)
This study examines Xaviera's cultural adaptation experience as an international student in South Korea through Fisher’s Narrative Paradigm Theory. Cultural adaptation is a complex adjustment process to norms, values, and social practices different from one’s original culture. This research uses qualitative methods and media semiotics to analyze the narrative Xaviera builds in a YouTube podcast by Raditya Dika. The study focuses on three main aspects of adaptation: language, stereotypes and self-identity, and learning patterns and ethos. The findings show that Xaviera’s narrative has strong coherence and credibility in describing her cultural adaptation process, effectively shaping the audience’s understanding and the self-image she wishes to convey. This study contributes to an understanding of the role of narrative in cultural adaptation and identity formation in the digital era, demonstrating that podcasts can be an effective medium for sharing cross-cultural experiences.Keywords – Cultural Adaptation, Narrative Paradigm, Podcast, Media Semiotics